THE USE OF WORD SEARCH GAME AS THE PRE-ACTIVITY IN TEACHING VOCABULARY - Ananda, Riska Julia; Suhartono, Luwandi; Rahmani, Eka Fajar (EDUPEDIA, 2024)
This study aimed to measure how significant is the effect of using the Word Search game as a pre-activity in improving the vocabulary mastery of fourth-grade students at SD Islam Mu’tashim Billah during the Academic Year 2023/2024. The research applied a pre-experimental one-group pre-test and post-test design, using a total sampling technique that selected 15 students from the tenth grade as the research sample. Analysis of the pre- and post-test data using a t-test revealed a pre-test mean score of 37.66 and a post-test mean score of 84.66. The t-test result, indicating -12.89, was compared to the t-table value of 1.761% at a 0.05 significance level with 14 degrees of freedom (df). Based on the above data analysis, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted because the t-test was smaller than the t-table (-12.89<-1.761). Furthermore, the effect size of 3.43 indicated a very strong effect (0.8<). In conclusion, the use of the Word Search game as a pre-activity in teaching significantly influences students' vocabulary mastery.